Down-Regulation of AHNAK2 Inhibits Cell Proliferation, Migration and Invasion Through Inactivating the MAPK Pathway in Lung Adenocarcinoma. (30th September 2020) - Wang, Dong-Wei; Zheng, Hai-Zheng; Cha, Na; Zhang, Xiao-Jie; Zheng, Min; Chen, Ming-Ming; Tian, Li-Xiang
AHNAK nucleoprotein 2 (AHNAK2) has been emerged as a crucial protein for neuroblast differentiation and cell migration, thereby involving in the development of various cancers. However, the specific molecular mechanism of AHNAK2 in lung adenocarcinoma is inconclusive. By accessing to the Oncomine dataset and GEPIA website, a higher expression level of AHNAK2 was observed in lung adenocarcinoma tissue samples. Overall survival (OS) curve plotted by Kaplan-Meier method showed that up-regulation of AHNAK2 was related with poor prognosis of lung adenocarcinoma patients. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis and western blot were conducted to examine the expression level of genes in lung adenocarcinoma cells. Through functional in vitro experiments, cell proliferation, migration and invasion were all suppressed after AHNAK2 knockdown using Cell counting kit-8 (CCK-8) assay, wound-healing and transwell analysis. Reduction of AHNAK2 decreased the apoptosis rate using flow cytometry analysis. Moreover, the key markers of MAPK pathway, p-MEK, p-ERK and p-P90RSK were decreased due to the transfection of si-AHNAK2 in A549 cells. U0126, a MEK inhibitor, showed the similar effects on MAPK-related protein levels with si-AHNAK2. To sum up, AHNAK2 is significantly increased in lung adenocarcinoma and plays a carcinogenic role by activating the MAPK signaling pathway, providing a novel insight and raising possibility for lung adenocarcinoma treatment.